Pengembangan Aplikasi Desktop Monitoring Kualitas Air Berbasis IoT untuk Pemantauan Parameter PH, Suhu, Salinitas dan TDS Secara Real-Time - Choirun Nisa (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2026)
This study aims to develop and implement an Internet of Things (IoT)-based desktop application for water quality monitoring capable of displaying real-time pH, temperature, salinity, Total Dissolved Solids (TDS), and sensor node location data. The application was developed using C# with the .NET WinForms framework and integrated with an Ardupilot Mega-based sensor system through serial communication using a 433 MHz 3DR radio module. The research adopted the Waterfall Software Development Life Cycle (SDLC), consisting of requirements analysis, system design, implementation, and testing. The application architecture comprises four main layers: data acquisition, data processing, data storage, and data presentation. Black-box testing confirmed that all functional requirements were successfully implemented, including serial communication, data parsing, real-time visualization, data logging, and Quality of Service (QoS) monitoring. The application presents monitoring data through numerical indicators, line charts, and historical graphs that update automatically. Performance evaluation showed an average data refresh time of 286.8 ms, a GUI response time of 118.5 ms, a throughput of 2,388.89 bps, and 0% packet loss, while the average transmission delay of 40.34 seconds indicates the need for further optimization. Additional features, including a monitoring session timer, real-time clock, and GPS distance indicator, enhance operational efficiency and support sustainable water quality monitoring.